First records in Italy of the red-listed shore bug Salda henschii (Reuter, 1891) (Hemiptera: Heteroptera: Saldidae) - Cianferoni, Fabio; Norbiato, Margherita; Dogliotti, Marco (Zootaxa, 2017)
Salda henschii (Reuter, 1891) is a boreo-montane species of Saldidae (Hemiptera: Heteroptera) restricted to mountain bogs and streams in central Europe (e.g., Western Carpathians, Alps) and to freshwater wetlands in lowland coastal areas in northern Europe (Fennoscandia); it is a vicariant of the arctic (Holarctic) element S. sahlbergi Reuter, 1875 (Hoberlandt 1977; Schuh et al. 1987; Péricart 1990; Lindskog 1991; Vinokurov 2010).